The Effect Of Using Different Rejected Watermelon On The Quality Of Bavarois Pudding - Haryanti, Haryanti; Anggraini, Ezi; Elida, Elida; Indrayeni, Wiwik (Jurnal Pendidikan Tata Boga dan Teknologi, 2024)
Bavarois pudding is a popular product with a sweet flavor and soft texture. This study aims to determine how the use of sengkaling rejected watermelon, oval rejected watermelon, and striped red rejected watermelon can affect the organoleptic characteristics of bavarois pudding. This type of research is pure experiment, the object of this research is pudding bavarois. The variables of this study include independent variables with 4 factors, namely no watermelon (X0), sengkaling rejected watermelon (X1), oval rejected watermelon (X2), and striped red rejected watermelon (X3). The dependent variable is the quality of bavarois pudding. The type of data is primary data sourced from 3 panelists who answered the organoleptic test format. This research design is a completely randomized design (CRD) with three repetitions. The data obtained were analyzed using analysis of variance (ANOVA), if Fcount > Ftable then continued with the Duncan test. The results showed that the use of rejected watermelon had a significant effect on the characteristics of shape, color, aroma, texture and taste. Striped red rejected watermelon had a significant effect on the characteristics of shape (neat according to the mold), color (pink), and taste of pudding bavarois (sweet watermelon). Oval ripe watermelon gave more prominent results in terms of texture (soft) and aroma (fragrant watermelon).